Tūpekepeke! Māori knowledge and practices in health and physical education : the perspectives, experiences and aspirations of secondary school teachers' : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Māori Studies at Massey University, Palmerston North, Aotearoa New Zealand - Tawhai, Daniel Tiotio Burfield (Massey University, 2016)
This thesis explores What are the perspectives, experiences and aspirations of secondary school Health and Physical Education teachers’ to better implement Māori knowledge and practices in their lessons? Individual, semi-structured, in-depth qualitative interviews were conducted with three secondary school Health and Physical Education (HPE) teachers with similar teaching experience, but different ethnic backgrounds. It was found that HPE teachers see Māori knowledge and practices as an effective way to enhance Māori student achievement, increase awareness of Māori culture amongst non-Māori students, and promote the overall development of Aotearoa New Zealand as a nation where indigenous knowledge and practices are a valued and contributing part of life and society. In order to achieve this, HPE teachers recommended development in teacher training programmes, professional development for practicing teachers’, and the development of resources and networks of teachers in the area of Māori knowledge and practices specific to HPE in Aotearoa New Zealand
Keywords: Physical education and training; Study and teaching (Secondary); Curriculum enrichment; New Zealand; Physical education teachers; Training of; Attitudes; Maori (New Zealand people); Social life and customs; Kura tuarua; Hākinakina; Hauora tinana; Mātauranga; Tikanga